Gender Performativity in Stieg Larsson’s 'The Girl with The Dragon Tattoo' - Supardan, Admiral Indra (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This study investigates the issue of gender performativity in Stieg Larsson’s novel The Girl With The Dragon Tattoo (2008). Judith Butler’s ideas on gender performativity serve as the theoretical framework of this study. A qualitative method is preferred as the study is heavily permeated with textual-analysis. The main objective of this study is to center on Larsson’s presentation of Lisbeth Salander in challenging boundaries in terms of how gender is presented and perceived. The study also provides analysis of other female characters, to see if they challenge or conform to the socially accepted notions of what it means to be a woman. The findings show that Stieg Larsson imbues his novel with the idea of challenging female stereotypes by developing fluidity within Salander’s gender identity. Larsson further ingrains gender performativity in all the female characters – they perform their gender identities differently in order to protect themselves from male-dominated society. However, the novel proves to be paradoxical as it shows an incessant reference to female characters in inferior circumstances. Keywords: Feminism, Gender, Identity, Performativity, Stereotypes